(untitled) (Revista Archai, 2019)
Our purpose on the present occasion is to evaluate some ideas the biographers of late antiquity held about the origins of European thought. Speaking about this period we are no longer dealing with the question of transferring of the archaic practices: these practices are indeed long dead. What we encounter can be better defined as the import of ideas. Equally important is a study of the changing attitudes of our authors: rather than passive witnesses, they became active participants of this import. The process is truly fascinating and we hope that the following examples, mostly from Hippolytus, will elucidate this. The best, almost a paradigmatic example is Pythagoras, who in late antiquity had many faces. His biography is an interesting instance of general change of attitude to ancient wisdom, typical for the source utilized by Hippolytus. Looking at a number of peculiar features of Hippolytus’ report which, we hope, will help us to see why the image of Pythagoras and his philosophy, formed by Hippolytus, is somewhat untypical for the period. We will see that Hippolytus’ biographic report, however garbled, shows no signs of so-called ‘Neopythagorean’ biographic development. Admittedly, the later authors frequently combine their sources to make them suitable to their needs, polemical or apologetic. Do we still have a reason to believe that these stories, however doubtful from the historical point of view, may contain the germs of truth?